The Neurobiology of Impulse Control Disorders - Williams, Wendol A. (2008)
OBJECTIVE: To review the neurobiological substrates of impulse control disorders (ICDs). Pathological gambling (PG) is a main focus of the review in that most biological studies of the formal ICDs have examined this disorder. METHODS: The medical database MedLine from 1966 to present was searched to identify relevant articles that were subsequently reviewed to generate this manuscript. RESULTS: Preclinical studies suggest that differential brain monoamine neuromodulation is associated with impulsive decision-making and risk-taking behaviors. Clinical studies implicate multiple neurotransmitter systems (serotonergic, dopaminergic, adrenergic, and opioidergic) in the pathophysiology of PG and other ICDs. Initial neuroimaging studies have implicated the ventromedial prefrontal cortex and ventral striatum in the pathophysiology of PG and other ICDs. Genetic contributions to PG seem substantial and initial studies have implicated specific allelic polymorphisms, although genome-wide analyses have yet to be published. CONCLUSION: Although significant advances have been made in our understanding of the neurobiology of ICDs, more research is needed to extend existing knowledge and translate these findings into clinical advances.